1999
DOI: 10.1046/j.1523-5378.1999.99274.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Treatment of Helicobacter pylori–Positive Duodenal Ulcer Using Pantoprazole at Low and High Doses Versus Omeprazole in Triple Therapy

Abstract: We found that 10-day triple therapy with amoxicillin, clarithromycin, and either pantoprazole, 80 mg daily, or omeprazole, 40 mg daily, is highly effective in ulcer healing and is very well tolerated, achieving the 90% cure recommended for an ideal first-line anti-H. pylori positive duodenal ulcer treatment regimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
3

Year Published

2001
2001
2008
2008

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 28 publications
0
21
0
3
Order By: Relevance
“…In our previous H. pylori eradication trials, we have demonstrated that double doses of PPIs were effective in inducing H. pylori -positive duodenal ulcer, while rabeprazole has shown to be efficacious in single dose (20 mg daily) as well as in double dose (40 mg daily), achieving an eradication and a healing rate as satisfactory as that of double-dose rabeprazole (40 mg) and omeprazole (40 mg daily) [10, 11, 12]. Several randomised controlled trials have compared short versus longer treatments [5, 29, 30, 31], but among these, only two studies comparing 2/4 days with 7/10 days have shown a significant difference [32, 33, 34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous H. pylori eradication trials, we have demonstrated that double doses of PPIs were effective in inducing H. pylori -positive duodenal ulcer, while rabeprazole has shown to be efficacious in single dose (20 mg daily) as well as in double dose (40 mg daily), achieving an eradication and a healing rate as satisfactory as that of double-dose rabeprazole (40 mg) and omeprazole (40 mg daily) [10, 11, 12]. Several randomised controlled trials have compared short versus longer treatments [5, 29, 30, 31], but among these, only two studies comparing 2/4 days with 7/10 days have shown a significant difference [32, 33, 34].…”
Section: Discussionmentioning
confidence: 99%
“…Various triple-therapy regimens, consisting in the association of a proton pump inhibitor (PPI) with two antimicrobials (clarithromycin, amoxicillin or metronidazole), have been reported to be effective and a high eradication rate of these different drug combinations have been confirmed in Western countries [5, 6, 7]. More recently, higher doses of PPI, such as lansoprazole- or pantoprazole-based triple therapy, have been shown to be more effective than low doses of PPI in many reports [4, 7, 8, 9, 10, 11, 12]. Rabeprazole, the new member of the class of substituted benzimidazole molecules, is a potent antisecretory agent, suppressing both basal and stimulated gastric acid secretion in a dose-dependent manner [13, 14, 15].…”
Section: Introductionmentioning
confidence: 99%
“…[87] The major result of the aforementioned metaanalysis comparing pantoprazole with other PPIs (such as omeprazole or lansoprazole) as eradication therapy against H. pylori is that the results are the same regardless of the PPI used. [78] Thus, as graphically presented in figure 2 derived from the seven studies [88][89][90][91][92][93][94] included in the meta-analysis in which 534 patients received pantoprazole and 603 patients received other PPIs, the mean H. pylori eradication rate was 83% and 81%, respectively. The OR for this comparison was exactly 1 (95% CI, 0.61-1.64).…”
Section: Pantoprazolementioning
confidence: 99%
“…Intention-to-treat analysis. [88][89][90][91][92][93][94] OR ¼ odds ratio; 95% CI ¼ 95% confidence interval.…”
Section: Rabeprazolementioning
confidence: 99%
“…2. Studies comparing pantoprazole-versus omeprazole-based triple therapies [8,11,13,14]. *Omeprazole or other PPI different from pantoprazole.…”
Section: Esomeprazolementioning
confidence: 99%